Teachers’ attitudes towards distance learning and its role in increasing students’ motivation in public schools in Zarqa Governorate in Jordan - Al-Alimi, Asma Muhyiddin (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify teachers’ attitudes towards distance learning and its role in increasing students’ motivation in public schools in Zarqa Governorate in Jordan and to identify the impact of the following variables (gender, specialization, and appreciation). To achieve the study’s goal, a questionnaire consisting of (20) items was developed, which was distributed to (70) male and female teachers, Teachers towards distance learning and its role in increasing students’ motivation in public schools in Zarqa Governorate in Jordan were significant, as it was found that there were no statistically significant differences at the significance level (α ≤ 0.05) between the average responses of the study sample members towards trends. Teachers towards distance learning and its role in increasing students’ motivation in public schools in Zarqa Governorate in Jordan due to the gender variable (gender, specialization, academic grade) and based on the results of this study, the researcher recommended recommendations One of the most important of these is the need to continue in distance e-learning in the future for subjects that do not require face-to-face meetings, and to enroll teachers in more training courses to increase their experience in dealing with the problems they face as a result of using distance education.
Keywords: distance learning; student motivation; Zarqa Governorate